An Analysis of Humanoid Robot Architecture, Uses, and the Future of the Industry (International Journal of Food and Nutritional Sciences, 2022)
Humanoid robots have captivated humans since the introduction of robotics. They are the physical manifestation of artificial intelligence. While human-like robots work independently in complicated human-populated worlds in science fiction, humanoid robots' capabilities are rather restricted in reality. AUTHOR will cover several exoskeleton technologies and also their significance in rehabilitation in this study. Based on several studies, this objective in rehabilitation seems to be promising. This study emphasizes the necessity for robots to exhibit human-like characteristics, as well as the specialized application of robotics. The last chapter of the magazine discusses human-humanoid control, as well as other technologies such as grabbing force. It also demonstrates the tendency in robotics research toward the construction of humanoid robots employing cogitative systems using artificial intelligence. The magazine concludes with a list of humanoid robot advances to help readers comprehend the depth of growth in the area of humanoid robots and the relevance of humanoid robots in the current and future eras.